PREVENTION OF CARDIOVASCULAR DISEASE AND CONSIDERABLE RISK FACTORS (World Bulletin of Public Health, 2025)
The article is illustrated information regarding to the study of different types of preventical methods , as well as , high risk factors . The paper considers the main factors how to influence cardiovascular system . Special attention is paid to global research methods , which make it possible to study in detail the amount of impacts and the process of effect mechanisms